UNCOVERING THE FACTORS DRIVING MSMES TO EMBRACE GREEN FINANCE: A STUDY IN SABAH, MALAYSIA - Chuong Shing, Chia; Caroline Geetha; Mat Salleh Hj Ayub (Malaysian Journal of Business and Economics (MJBE), 2024)
Green economy is an alternative path to accomplish sustainable development using green financing. Despite the Malaysian government has introduced various green funding, the participation from the Micro, Small and Medium-sized industries (MSMEs) is still considerably low. Therefore, this study sought to explore the predictors that influence the purchase of green financing among services and manufacturing MSMEs owners in Sabah. Guided by the theory of planned behavior (TPB), a research model was established, consisting of attitude, subjective norm, and perceived behavioral control. In addition, the theory of decision-making under uncertainty and theory of environmental attitude were incorporated in the present research model to build and measure the general attitude within the TPB framework. Using purposive sampling technique, the data was collected from a cross-sectional sample of 147 MSME owners through an online self-administrated questionnaire. Moreover, the research model was assessed using a PLS-based structural equation modelling technique to examine the hypothesized relationships. The findings highlighted that the constructs of TPB exert significant relationship on the behavioral intention except for subjective norm. Perceived behavioral control was also evidenced as a highly significant predictor of behavioral intention, followed by attitude.